Tinjauan Strategi Umpan Balik Korektif dalam Proses Pembelajaran Filsafat Penjasorkes pada Mahasiswa PJKR UKAW: Tinjauan Strategi Umpan Balik Korektif dalam Pembelajaran Filsafat Penjasorkes pada Mahasiswa PJKR UKAW - Talan, Rudobertus; Nay, Florianus Aloysius; Belipati, Arisona Benyamin (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of   the  study. This study aims to determine the corrective feedback strategy in the learning process of physical education and health philosophy in PJKR UKAW students. Materials and methods. The method used in this research is quantitative method with quantitative descriptive research type. Results .The results obtained in this study, from the total sample of 65 PJKR UKAW students who were in the unsuitable category of 3.07% as many as 2 people, and those in the appropriate category of 40% as many as 26 people while those in the very category according to 56.92% as many as 37 people. Conclusions.. Based on the results of these studies, it can be concluded that the Corrective Feedback Strategy, can be categorized as very suitable to be used in the physical education philosophy learning process for UKAW PJKR students.